2007
DOI: 10.1111/j.1472-765x.2007.02229.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane filtration method for enumeration and isolation of Alicyclobacillus spp. from apple juice

Abstract: Aim:  To evaluate the applicability of filtration membranes for detecting Alicyclobacillus spp. spores in apple juice. Methods and Results:  Ten types of nitrocellulose membrane filters from five manufacturers were used to collect and enumerate five Alicyclobacillus spore isolates and results were compared to conventional K agar plating. Spore recovery differed among filters with an average recovery rate of 126·2%. Recovery levels also differed among spore isolates. Although significant difference (P < 0·05) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…counting from juices was troublesome at the tested concentrations. In literature bacterial enumeration at low concentrations is reported as imprecise and difficult (Duvenage, 2006;Lee, Chang, Shin, & Kang, 2007). Consequently, in peach and orange juices, it can only be stated that EOS 835 was able to detect contamination in samples inoculated 24 h earlier with as little as 10 and <10 2 c.f.u./ml respectively.…”
Section: Discussionmentioning
confidence: 96%
“…counting from juices was troublesome at the tested concentrations. In literature bacterial enumeration at low concentrations is reported as imprecise and difficult (Duvenage, 2006;Lee, Chang, Shin, & Kang, 2007). Consequently, in peach and orange juices, it can only be stated that EOS 835 was able to detect contamination in samples inoculated 24 h earlier with as little as 10 and <10 2 c.f.u./ml respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Some loss of spores through filtration is not unusual. Lee et al (11) found that recovery of Alicyclobacillus varied greatly among filter brands and pore sizes.…”
Section: Resultsmentioning
confidence: 98%
“…The composition and structure of the membrane specific to the manufacturer may also affect the efficiency of spore recovery of spores. Lee et al (2007) reported that membranes with the same pore size but from different manufacturers produced significantly different results. Membrane filtration is also not suitable for all products, e.g., dense fruit juice concentrates and liquids that are not clear (Jensen, 1999).…”
Section: Effect Of the Plating Techniquementioning
confidence: 96%
“…Nevertheless, the membrane filtration method has some disadvantages. Lee et al (2007) investigated the use of different filtration membranes for the recovery of Alicyclobacillus spores in apple juice. The application of filtration membranes with two different pore sizes (0.22 and 0.45 μm) obtained from five manufacturers was evaluated and compared with conventional spread plating on K agar.…”
Section: Effect Of the Plating Techniquementioning
confidence: 99%
See 1 more Smart Citation